Multiple Magnets Ingestion Followed by Intestinal Fistula With Mild Symptoms. (June 2019) - Miyamoto, Ryosuke; Okuda, Masumi; Kaneko, Kenitiro; Numoto, Shingo; Okumura, Akihisa
A healthy 3-year-old boy visited our hospital because of abdominal pain and vomiting, and abdominal X-ray revealed a 10 mm non-sharp foreign body in the lower abdomen. No one had witnessed accidental ingestion. Abdominal symptoms were mild. We followed-up with abdominal X-rays, but the foreign matter did not move. His grandfather remembered that he was playing with a posting magnet. Thus, the foreign matter was considered to be multiple magnets. No foreign body was excreted by laxative administration. There was no foreign matter revealed even by the colonoscopy. Because a fistula was found in the ileum, it was diagnosed as gastrointestinal perforation. Three magnets adhered from inside the fistula were removed by emergency laparotomy surgery. The final diagnosis was ileal sigmoid fistula due to damage of the mucous membrane sandwiched between the magnets. Multiple magnet ingestion often causes gastrointestinal injury. Even if the symptoms are mild, it should be removed promptly.